PELAKU PENAMBANGAN PASIR LAUT SEBAGAI PERBUATAN MELAWAN HUKUM PIDANA DAN KENDALA HUKUMNYA - Lopmeta, Arwan Y; Pello, Jimmy; Wilhelmus, Bhisa Vitus (Petitum Law Journal, 2024)
Sand is a natural marine resource that is very important for protecting island coastal areas. Nowadays, sea sand is often taken by truck owners to sell as building materials. Coastal Law on the Sea with a prohibition on Mining Beach Sea Sand. This research is included in the type of normative juridical research with a research approach, casuistry approach. The results of research in the field show: Sea sand mining can be punished according to Law No. 27 of 2007 concerning the management of coastal areas and small islands. Article 35 i carry out sand mining in areas which technically, ecologically, socially and culturally cause environmental damage and environmental pollution and harm the surrounding community. East Nusa Tenggara Province Regional Regulation No. 2 of 2019 concerning the implementation of peace, public order and protection of the regional mining business community for class C minerals. Paragraph VI Article 38: Everyone is prohibited from taking sea sand and coral reefs which damage the environmental sustainability of marine biota in offshore waters. (2) the obstacle in overcoming sea sand mining is the lack of public awareness of the law and economic factors. Based on the results of the research achieved, several things can be concluded, namely that the actions of sea sand miners can be seen as an act against criminal law because against the law is an act that violates the law, an act carried out outside the power or authority as well as an act that violates general principles in the field of law.